KANDUNGAN Cu DAN Pb PADA AIR DAN IKAN PUYAU (Puntius huguenini) DI BENDUNGAN SUNGAI TABANIAO DESA BAJUIN KECAMATAN PELAIHARI KABUPATEN TANAH LAUT - Bunda Halang (Bioscientiae, 2007)
Mining has been demonstrated to lead to environmental pollution of heavy metals. The present study was aimed to assess the impact of iron and gold mining activities around Tabaniao River on the water quality. Cu and Pb levels of the river water was examined as well as the levels on the flesh of the indigenous puyau fish. Water and fish samples were collected from a dam of water supply plant at Tabanio River. Cu and Pb levels were determined by atomic absorption spectrophotometry (AAS). The analyses showed estimates of  0.0042 mg/l and 0.0201 mg/l concentrations of Cu and Pb in the water, and < 0.002 mg/kg and < 0.0037 mg/kg levels of Cu and Pb in fish. It was then concluded that the levels of both heavy metals were still below threshold.